Replication fork reversal triggers fork degradation in BRCA2-defective cells - Mijic, Sofija; Zellweger, Ralph; Chappidi, Nagaraja; Berti, Matteo; Jacobs, Kurt; Mutreja, Karun; Ursich, Sebastian; Ray Chaudhuri, Arnab; Nussenzweig, Andre; Janscak, Pavel; Lopes, Massimo (Nature communications, 2017)
Besides its role in homologous recombination, the tumor suppressor BRCA2 protects stalled replication forks from nucleolytic degradation. Defective fork stability contributes to chemotherapeutic sensitivity of BRCA2 -defective tumors by yet-elusive mechanisms. Using DNA fiber spreading and direct visualization of replication intermediates, we report that reversed replication forks are entry points for fork degradation in BRCA2 -defective cells. Besides MRE11 and PTIP, we show that RAD52 promotes stalled fork degradation and chromosomal breakage in BRCA2 -defective cells. Inactivation of these factors restores reversed fork frequency and chromosome integrity in BRCA2 -defective cells. Conversely, impairing fork reversal prevents fork degradation, but increases chromosomal breakage, uncoupling fork protection, and chromosome stability. We propose that BRCA2 is dispensable for RAD51-mediated fork reversal, but assembles stable RAD51 nucleofilaments on regressed arms, to protect them from degradation. Our data uncover the physiopathological relevance of fork reversal and illuminate a complex interplay of homologous recombination factors in fork remodeling and stability. BRCA2 is involved in both homologous recombination (HR) and the protection of stalled replication forks from degradation. Here the authors reveal how HR factors cooperate in fork remodeling, showing that BRCA2 supports RAD51 loading on the regressed arms of reversed replication forks to protect them from degradation.